Group A Streptococcus Septic Shock after Surgical Abortion: A Case Report and Review of the Literature. (11th September 2017) - Tardieu, Stephanie C.; Schmidt, Elizabeth
Abstract : Group A Streptococcus (GAS) causing puerperal sepsis is a leading cause of maternal mortality worldwide. Although rare, GAS infection is a relatively significant public health concern because of its propensity to evolve rapidly into septic shock, streptococcal toxic shock syndrome, and death. We report the case of a 27-year-old patient who presented with GAS septic shock after undergoing a surgical termination of pregnancy and was treated successfully and recovered without sequelae. GAS septic shock should always be included in the differential diagnosis of any patient who develops sepsis after a surgical abortion. Patients with GAS septic shock have a rapid clinical decline and need aggressive fluid management, early initiation of broad-spectrum antibiotics, and rapid surgical intervention.